STRAIGHTENING TOOL «INDUCTOR SYSTEM WITH AN ATTRACTING SCREEN» AND LENGTHY SOLENOID - Yu. Batyhin; Ye. Chaplyhin; M. Barbashova; O. Gavrilova (Avtomobilʹnyj Transport (Harʹkov), 2017)
The article presents the analysis of electrodynamic processes in the «inductor system with an attracting screen». Its design is presented by a cylindrical multi-turn solenoid at the end of which various thin-walled sheet metals are attached. Estimates of excitation efficiency of electrodynamic attracting forces are presented. The adequacy of Physics and mathematical model is provided by taking into account the inductor geometry, its location and diffusion effects.